S20 Primary Result of the 1st Therapeutic Interventions in Malignant Effusion (TIME1) Trial: A 2 × 2 factorial, randomised trial of chest tube size and analgesic strategy for pleurodesis in malignant pleural effusion. (12th November 2015) - Rahman, NM; Pepperell, J; Rehal, S; Saba, T; Tang, A; Ali, N; West, A; Hettiarachchi, G; Mukherjee, D; Samuel, J; Bentley, A; Dowson, L; et al.
Abstract : Background: Optimal management of pleurodesis for malignant pleural effusion (MPE) has not been defined either in terms of optimal analgesia or chest tube size. Non-steroidal anti-inflammatory drugs (NSAID) are highly effective analgesics, but are avoided in pleurodesis as they may reduce pleurodesis efficacy. Smaller (<14 French) chest tubes may be less painful compared to larger chest tubes, but their efficacy in MPE pleurodesis has not been proven. This study investigated chest tube size (large versus small) and analgesia (NSAID versus opiate) in this setting. Methods: A 2 × 2 factorial, phase 3 randomised controlled trial in 320 patients with MPE undergoing pleurodesis. Patients were randomised to opiate/NSAID and 24 French drain/12 French drain. Co-primary outcomes were; pain while tube in situ, measured on 100 mm visual analogue scale (VAS) over 5 days (superiority comparison) and pleurodesis efficacy at 3 months (non-inferiority comparison, margin of non-inferiority 15%). Secondary outcomes included use of rescue analgesia, pleurodesis success to 6 months, adverse events and mortality. Results: 320 patients were randomised (63% male, mean age 71.8 years), with similar baseline characteristics. Mean VAS scores in opiate and NSAID groups were similar (adjusted mean difference, -1.5 mm (95% confidence interval [CI], -5.0 to 2.0; p = 0.40). Patients receiving NSAID required more rescue analgesia (38% vs. 26%). Pleurodesis failure occurred in 33/144 (23%) NSAID patients compared with 30/150 (20%) of participants receiving opiate, meeting criteria (15%) for non-inferiority (difference 3%; (90% CI -5% to 10%)). Smaller chest tubes were modestly less painful than larger tubes (adjusted mean difference, -6.0 mm (95% CI, -11.7 to -0.2; p = 0.04)) and were associated with a higher pleurodesis failure rate which failed to meet non-inferiority criteria (pleurodesis failure 15/50 (30%) and 12/50 (24%) respectively, difference 6% (90% CI, -9% to 20%)). Adverse events did not differ between analgesic groups, but complications during insertion occurred more commonly with smaller drains (adjusted odds ratio, 1.91; 95% CI 0.71 to 5.13, p = 0.20). Conclusion: NSAID and opiate analgesia were not significantly different in treatment of post-pleurodesis pain and neither was associated with impaired efficacy of pleurodesis. Smaller chest tubes were associated with less pain, but may be associated with reduced pleurodesis success compared with larger tubes. These results challenge current guidelines for pleurodesis of MPE, which advocate avoidance of NSAID and use of small chest tubes.